Optic Nerve Canal Variations in Relation to Posterior Para Nasal Sinus In Indians: A Review-Based Classification Approach - M, Desanesan; Sundararajan, S; Keerthi, B H Parameshwar; S, Sasidharan; Priya, Lakshmi (Journal of Neonatal Surgery, 2025)
Background: The optic nerve canal (ONC), as it travels from the orbit to the cranial cavity, lies in close anatomical proximity to the Posterior paranasal sinus (PNS)—particularly the sphenoid and posterior ethmoid sinuses. This relationship is critical during functional endoscopic sinus surgery (FESS) and skull base procedures. Anatomical variations of the ONC can increase the risk of surgical complications such as optic nerve injury and potential vision loss. Despite the clinical importance, limited data exist on these variations in the Indian population, where ethnic and genetic diversity may influence cranial anatomy. Our study aims to classify variations of the optic nerve canal in relation to posterior PNS in Indian ethnics. Methods: This review synthesizes findings from multiple computed tomography (CT)-based observational studies focusing on the ONC's course relative to posterior PNS in Indian subjects. The Delano classification system was used to categorize ONC types, and additional anatomical features such as bone dehiscence and anterior clinoid process pneumatization (PACP) were analysed. Results: Among 300 optic nerve canals reviewed, Type I (no indentation/protrusion) was the most common (65.3%), followed by Type II (18.0%), Type III (9.6%), and Type IV (7.0%). Bone dehiscence was present in 7.3% of canals, most frequently in Type III (27.5%). PACP was found in 14.3%, most common in Type III (34.4%). ONC symmetry was observed in 91.25% of subjects, while asymmetry was noted in 8.75%. Conclusion: This review emphasizes the need for detailed preoperative imaging and anatomical assessment in Indian patients undergoing sinus or skull base surgeries. The application of a simplified classification system based on CT imaging enhances surgical planning, helps to avoid optic nerve injury and contributes safer clinical outcomes.